Entry Academic Scores as a Predictor of Terminal Academic Achievement among Students in Primary Teachers’ Colleges in South-Western Uganda - Nuwagaba, James; Mwesigye, Adrian Rwekaza; Karoro, Emmanuel (East African Journal of Education Studies, 2022)
The purpose of the research was to establish the influence of entry scores on students’ performance in final examinations in primary teachers’ colleges in South Western Uganda. The research anchored on postpositivist philosophy adopted a cohort longitudinal survey research design incorporating correlational techniques. The research employed quantitative methods of data collection in nine government-aided PTCs in South Western Uganda. The sample size was 214 students obtained using simple random sampling from 1192 students in the nine primary teachers’ colleges. Data were collected using closed-ended questionnaires and document analysis guides, and it was analysed using SPSS version 20. Research findings revealed that there was no statistically significant relationship between entry scores and academic performance (r = - .012, p = .864) of students in primary teachers’ colleges in South Western Uganda. From the findings, it was concluded that failure in academics in PTCs can be minimised by strengthening the training (teaching and learning), not increasing entry cores. The study recommended that the policy on entry into PTCs should be revised to include other factors like the candidate’s interest, attitude, talents etc. and lessen the emphasis on the scores one obtained at the previous academic level